Negative Diffusion Weighted Imaging After IV tPA is Rare and Unlikely To Indicate Averted Infarction - Freeman, Jason W. (2013)
BACKGROUND AND PURPOSE: Some patients treated with IV tPA have negative diffusion-weighted imaging (DWI) on follow-up imaging. Without a visible infarct, there may be uncertainty as to whether the patient was having a stroke that was averted by tPA or whether the symptoms had not been cerebrovascular in origin. We evaluated patients presenting with suspected acute stroke with a positive DWI lesion prior to IV tPA to determine the probability of finding a negative DWI up to 48 hours after treatment. METHODS: We included patients from the Lesion Evolution in Stroke and Ischemia On Neuroimaging (LESION) Project who had acute MRI screening with a positive DWI lesion before IV tPA treatment and had follow-up MRI up to 48 hours later. Experienced readers interpreted all acute and follow-up MRIs looking for ischemic lesions on DWI. RESULTS: There were 231 patients who met study inclusion criteria, of which 225 patients (97.4%) had a persistent positive DWI corresponding to the acute stroke lesion on all follow-up imaging. Four patients (1.7%) had transient DWI lesion reversal with positive DWI on subsequent follow-up imaging. There were only 2 cases (0.9%) of complete DWI lesion reversal on all follow-up imaging. CONCLUSIONS: Averted infarction following IV tPA is rare, occurring in 0.9% of patients with pre-treatment positive DWI evidence of acute ischemia. For IV tPA-treated patients who have a negative DWI on follow-up imaging, a cause other than acute stroke should be explored.